Aflibercept 5+PRN with retinal laser photocoagulation is more effective than retinal laser photocoagulation alone and aflibercept 3+PRN with retinal laser photocoagulation in patients with high-risk proliferative diabetic retinopathy and diabetic macular edema: a 12-month clinical trial - Li, Shuting; Tao, Yuan; Yang, Mengyao; Zhao, Hui; Si, Mingwei; Cui, Wenxuan; Wang, Hong (Frontiers in Endocrinology, 2024)
Objective: This study aimed to investigate and compare the efficacy and safety of retinal laser photocoagulation (PRP) alone, PRP with aflibercept 3+PRN, and PRP with aflibercept 5+PRN in patients with both high-risk proliferative diabetic retinopathy (PDR) and diabetic macular edema (DME).Methods: Overall, 170 patients with high-risk PDR and DME (170 eyes from 170 patients) who visited our ophthalmology clinic from December 2018 to December 2020 were divided into the PRP (n=58), aflibercept 5+PRN with PRP (n=53), and aflibercept 3+PRN with PRP (n= 59) groups.General information, such as age, sex, and eye category, was obtained. Moreover, best-corrected visual acuity (BCVA), baseline central macular foveal thickness (CFT), microaneurysm (MA), area of neovascularization (NV), area of hard exudate (HE), and cytokine levels in atrial fluid before and after treatment, were assessed. Differences were considered statistically significant at P < 0.05. The BCVA (log MAR) decreased from 0.72±0.17 and 0.74±0.17 to 0.50±0.13 and 0.53±0.17 in PRP with aflibercept 5+PRN and PRP with aflibercept 3+PRN groups, respectively, with a statistically significant difference compared to those in the PRP group (P<0.05 in all cases). The CFT in the PRP-only group decreased slightly from 361.80±36.70 μm to 353.86±40.88 μm, with no statistically significant difference (P>0.05), whereas the CFT in the aflibercept 5+PRN with PRP and aflibercept 3+PRN with PRP groups decreased from 356.57±37.57 μm and 358.17±44.66 μm to 284.87±31.52 μm and 303.19±37.00 μm, respectively, with statistically significant differences before and after treatment. The number of MA (pcs) in the PRP, aflibercept 5+PRN with PRP, and aflibercept 3+PRN with PRP groups decreased from 118. 34±27.96, 118.60±33.34, and 116.59±28.95 to 92.95±29.04, 44.60±20.73, and 54.26±25.43, respectively. In the three groups, NV decreased from 1.00±0.21 mm², 1.01±0.18 mm², and 0.98±0.20 mm² before treatment to 0.49±0.17 mm², 0.31±0.16 mm², and 0.38±0.14 mm², respectively, with statistically significant differences.After 12 months of treatment, 13, 18, and 18 patients had reduced HE area in the PRP-only, aflibercept 5+PRN with PRP. After 12 months of treatment, vascular endothelial growth factor, monocyte chemoattractant protein-1, and glial fibrilliary acidic protein levels (pg/mL) in the aqueous humor decreased in both combined treatment groups compared with that at baseline.